A Threshold for Timing Applications of IGRs to Manage the Silverleaf Whitefly and Irregular Ripening on Tomato - David J. Schuster (EDIS)
The silverleaf whitefly, Bemisia argentifolii Bellows & Perring, has been the major pest of tomatoes in South Florida since 1988 (Schuster et al. 1989). The insect causes losses indirectly through the transmission of plant viruses, including Tomato mottle virus and Tomato yellow leaf curl virus in Florida (Simone et al. 1990, Polston et al. 1999). Feeding, primarily by nymphs, has been associated with an irregular ripening (IRR) disorder of fruit (Schuster et al. 1990, Schuster 2002). The disorder is characterized externally by inhibited or incomplete ripening of longitudinal sections of fruit and internally by an increase in the amount of white tissue. No foliar symptoms are apparent. This document is ENY705, a publication of the Entomology and Nematology Sciences Department, Florida Cooperative Extension Serivce, IFAS, University of Florida. Publication date: March 2004.